2009
DOI: 10.1016/s2255-4971(15)30070-7
|View full text |Cite
|
Sign up to set email alerts
|

Sprengel's Deformity: Surgical Correction by a Modified Green Procedure

Abstract: Objective: To evaluate the cosmetic and functional results of patients submitted to surgical correction of Congenital High Scapula (Sprengel's Deformity) using modified Green's Procedure, as well as patients' satisfaction and complications. Methods: Nine patients submitted to surgical treatment from September 1993 to April 2008 have been assessed. The modification from original technique was: subperiosteal muscle detachment, resection of superomedial scapular portion and fixation of medial portion of scapular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Most studies reported the patients’ sex, except three [ 34 , 43 , 57 ], and the affected side, except eight [ 21 , 23 , 43 , 47 , 50 , 54 , 57 , 59 ]. In the preoperative evaluation, 28 studies classified patients according to the Cavendish clinical scoring system [ 2 , 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 33 , 35 , 36 , 37 , 38 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 55 , 58 , 59 , 60 ] and 15 studies [ 14 , 15 , 16 , 17 , 19 , 21 , 32 , 36 , 41 , 45 , 48 , 53 , 57 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies reported the patients’ sex, except three [ 34 , 43 , 57 ], and the affected side, except eight [ 21 , 23 , 43 , 47 , 50 , 54 , 57 , 59 ]. In the preoperative evaluation, 28 studies classified patients according to the Cavendish clinical scoring system [ 2 , 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 33 , 35 , 36 , 37 , 38 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 55 , 58 , 59 , 60 ] and 15 studies [ 14 , 15 , 16 , 17 , 19 , 21 , 32 , 36 , 41 , 45 , 48 , 53 , 57 ,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies (441 patients) reported the grade of deformity, according to the Cavendish classification [ 9 , 14 , 16 , 17 , 19 , 20 , 21 , 23 , 35 , 36 , 37 , 41 , 42 , 44 , 45 , 46 , 48 , 52 , 53 , 55 , 58 , 59 , 60 ]. Ninety-seven patients (22%) were grade 4, 283 patients (64.2%) were grade 3, 51 patients (11.5%) were grade 2 and 10 patients (2.3%) were grade 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations